2015
DOI: 10.1080/00036846.2015.1071476
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of price reaction to rights issue announcements in the Kuwait Stock Exchange

Abstract: This study examines the drivers behind stock price reactions to announcements of rights issues by firms listed on the Kuwaiti Stock Exchange for the period 2003-2013. We find higher cumulative abnormal returns for firms that undertake larger issues, with the issue size reflecting the availability of favourable investment opportunities and their potential positive impact on firms' earnings. We also document a positive price reaction in firms that are affiliated with a family group. We interpret this as evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
(80 reference statements)
1
3
0
Order By: Relevance
“…This means that the CAR level for the pooled sample does not change according to the leverage level of companies. Findings of ANOVA analysis are in line with Tan et al (2002) and Alhashel and Alojayan (2015).…”
Section: Empirical Findingssupporting
confidence: 74%
See 2 more Smart Citations
“…This means that the CAR level for the pooled sample does not change according to the leverage level of companies. Findings of ANOVA analysis are in line with Tan et al (2002) and Alhashel and Alojayan (2015).…”
Section: Empirical Findingssupporting
confidence: 74%
“…For example, the average participation rate by investors in rights issues is 64% in the USA. On the other hand, a positive excess return is reported in Japan by Kang and Stulz (1996), which is around 2.20% for (−1, 1) event window; in Greece by Tsangarakis (1996), which is about 3.90% for (−1, 0); in Singapore by Tan et al (2002), which is approximately 2% within 3-day event window; and in Kuwait by Alhashel and Alojayan (2015), which is around %5 for (−2, 2). Ariff et al (2007) assert that rights issue announcements can be perceived as favourable if the appetite for high growth exists in a country.…”
Section: Introduction and Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…In the literature, the right issues are often followed by the discussion on how the market responds to the offerings. Some researchers found a positive response to the issuance of rights (Alhashel and Alojayan, 2015;Ariff et al, 2007;Paskelian and Bell, 2010), while some others found a negative response (Akron, 2013; Barnes and Walker, 2006;Feng et al, 2018;Iqbal, 2008;Krishnan et al, 2010). Some researchers explain these different responses by a variety of approaches, including by associating them with variations in the motivation of right offerings among companies (Brisker et al, 2014;Kim and Purnanandam, 2014;Veld et al, 2018;Yang et al, 2016), variations of inherent attributes in the issuers (Chan and Walter, 2014;Chen, 2017;Dutordoir et al, 2018;Fu and Huang, 2016;Liu et al, 2016;Naveen et al, 2018), and variations of investor biases in responding to the rights (Devos et al, 2017;Dutta, 2017;Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%